2015
DOI: 10.1016/j.bmc.2015.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antibacterial activities of cadiolides A, B and C and analogues

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
0
12
0
2
Order By: Relevance
“…These biomarkers, associated with epithelial-derived cell lines and also some colorectal, breast and lung cell lines, could be of use in predicting the likelihood of patient response to didemnin B or analogues in a therapeutic setting. Synthetic analogues related to the polyandrocarpamines 955 were found to be inhibitors of H 2 S production by cystathionine beta-synthase, 956 and SAR studies have been reported for thiaplidiaquinones A and B 957 (various biological targets), 958 cadiolides A-C 959,960 (antibacterial), 961,962 rubrolides 963 (photosynthesis inhibitors), 964 meridianins 965 (antimalarial and antituberculosis), 966 isogranulatimide 967 (cytotoxicity), 968 and lamellarins 969 (cytotoxicity). 970…”
Section: Molluscsmentioning
confidence: 99%
“…These biomarkers, associated with epithelial-derived cell lines and also some colorectal, breast and lung cell lines, could be of use in predicting the likelihood of patient response to didemnin B or analogues in a therapeutic setting. Synthetic analogues related to the polyandrocarpamines 955 were found to be inhibitors of H 2 S production by cystathionine beta-synthase, 956 and SAR studies have been reported for thiaplidiaquinones A and B 957 (various biological targets), 958 cadiolides A-C 959,960 (antibacterial), 961,962 rubrolides 963 (photosynthesis inhibitors), 964 meridianins 965 (antimalarial and antituberculosis), 966 isogranulatimide 967 (cytotoxicity), 968 and lamellarins 969 (cytotoxicity). 970…”
Section: Molluscsmentioning
confidence: 99%
“…Still in 2015, Franck and coworkers synthesized some analogues of cadiolide A (359a), cadiolide B (359b) and cadiolide C (359c) ( Figure 25) [213], three brominated, densely functionalized 2(5H)-furanone derivatives which were isolated in 1998 from an Indonesian ascidian of the genus Botryllus [214] and in 2012 from the Korean tunicate Pseudodistoma antiboja [215]. Interestingly, a similar one-pot procedure was used to prepare cadiolide analogues 363, 364 and 365 ( Figure 26) in 38%, 37% and 30% yield, respectively [213]. BF-14) and (E)-4-bromo-5-(bromomethylene)-3-methyl-2(5H)-furanone (249) (BF-8) in 12%, 2.7% and 13% yield, respectively (Scheme 90) [174].…”
Section: Scheme 121 Enantioselective Synthesis Of Anti-2(5h)furanonementioning
confidence: 99%
“…Furthermore, in 2015, cadiolides C (359c) and A (359a) were synthesized by Franck and coworkers [213] by using the one-pot reaction of a-hydroxyketones, dioxinones and aryl aldehydes, which they had previously employed in the synthesis of cadiolide B (359b) [223]. As shown in Scheme 132, cadiolide C (359c) was obtained in 47% yield by reacting 1.0 equiv of a-hydroxyketone 359, 2.0 equiv of dioxinone 408 and 1.0 equiv of aldehyde 228 with 2.0 equiv of Et 3 N in toluene under microwave irradiation at 150 °C for 5 min and treatment of the resulting reaction mixture with 1 M HCl followed by BBr 3 -mediated Odemethylation of the resulting product [230].…”
Section: Scheme 128 Synthesis Of Rubrolide a Diacetate (390)mentioning
confidence: 99%
“…10,[11][12][13][14][15] Em função das atividades listadas anteriormente, várias estratégias de síntese foram desenvolvidas para esses compostos (Esquema 1). [15][16][17][18] A primeira síntese total de um cadiolídeo foi relatada em 2005 (Esquema 1, Estratégia 1). Neste trabalho, o cadiolídeo B foi sintetizado a partir da lactona 4-bromofuran-2(5H)-ona (1), gerando os intermediários 2 e 3, em 42% de rendimento global.…”
Section: Introductionunclassified
“…15 Outra abordagem para obtenção do intermediário 3 foi relatada para a síntese dos cadiolídeos A, B e C, utilizando um processo multicomponente envolvendo o intermediário 4 como o passo proeminente (Esquema 1, Estratégia 2). 16,17 Uma das metodologias mais elegantes para a síntese dos cadiolídeos A, B e D, utiliza como etapa-chave para a construção do núcleo β-aril-α-benzoilbutenolídeo (2), foi uma reação de cicloadição/ cicloreversão de Diels-Alder entre a inona 5 e o oxazol 6. 18 Esta etapa-chave ocorre em alto rendimento (70%), e o intermediário 2 é submetido a uma reação de condensação de Knoevenagel viníloga com benzaldeídos (Esquema 1, Estratégia 3).…”
Section: Introductionunclassified